Negative electrode active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery comprising the same
Patent Information
- Application Number
- CN202610545884.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-30
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-30
Smart Images

Figure CN123017908A_ABST
Abstract
Description
[0001] This application claims priority and benefit to Korean Patent Application No. 10-2025-0057549, filed on April 30, 2025, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field
[0002] This disclosure relates to a negative electrode active material for a rechargeable lithium battery, a method for preparing the negative electrode active material, and a rechargeable lithium battery including the negative electrode active material. Background Technology
[0003] With the rapid proliferation of battery-powered electronic devices such as mobile phones, laptops, and electric vehicles, the demand for rechargeable batteries with high energy density and capacity has increased rapidly. As a result, research and development efforts have been undertaken to improve the performance of rechargeable lithium-ion batteries.
[0004] A rechargeable lithium battery includes a positive electrode and a negative electrode containing active materials capable of inserting and deintercalating lithium ions. The rechargeable lithium battery generates electrical energy through redox reactions that occur when lithium ions are deintercalated from the negative electrode and inserted into the positive electrode, and vice versa. Summary of the Invention
[0005] One embodiment aims to provide a negative electrode active material for a rechargeable lithium battery with a low oxygen concentration.
[0006] Another embodiment aims to provide a method for preparing a negative electrode active material for a rechargeable lithium battery, wherein the method has a shortened grinding time for silicon precursor particles.
[0007] One embodiment provides a negative electrode active material for a rechargeable lithium battery, the negative electrode active material comprising a silicon-carbon composite containing silicon nanoparticles and amorphous carbon, wherein the silicon-carbon composite has an oxygen content of 10 wt% or less, and the silicon nanoparticles have an average size D50 of 10 nm to 200 nm.
[0008] Another embodiment provides a method for preparing a negative electrode active material for a rechargeable lithium battery, the method comprising the steps of: preparing silicon nanoparticles and mixing the silicon nanoparticles or assemblies of silicon nanoparticles with an amorphous carbon precursor and subjecting them to heat treatment, wherein the step of preparing silicon nanoparticles includes grinding silicon precursor particles in a solvent with a viscosity of 0.1 mPa·s to 0.5 mPa·s at 25°C.
[0009] Another embodiment provides a rechargeable lithium battery including a negative electrode and a positive electrode, the negative electrode including the negative electrode active material for the rechargeable lithium battery. Attached Figure Description
[0010] The above and other objects, features and advantages of this disclosure will become more apparent to those skilled in the art by referring to the accompanying drawings and describing in detail the exemplary embodiments thereof.
[0011] Figures 1 to 4 This is a schematic cross-sectional view of a rechargeable lithium battery according to an embodiment. Detailed Implementation
[0012] The embodiments of this disclosure will be described in detail below.
[0013] Unless otherwise stated herein, when a component such as a layer, membrane, region, or plate is described as being “on” another component, this includes not only the case where the component is “directly on” another component, but also the case where another component is present in between.
[0014] Unless otherwise specified, a singular expression may also include a plural expression. Additionally, unless otherwise specified, "A or B" may mean "including A, including B, or including both A and B".
[0015] In the specification, "the combination thereof" can refer to mixtures, laminates, composites, copolymers, alloys, blends and reaction products of the components.
[0016] In the specification, "particle size D50" and "average size (or average particle diameter) D50" refer to the average particle size representing the size of particles that constitute 50% of the cumulative volume in the particle size distribution. Particle size distribution can be measured by methods known to those skilled in the art. For example, it can be measured using a particle size analyzer or by transmission electron microscopy or scanning electron microscopy. Alternatively, by using a measuring device utilizing dynamic light scattering, particle size can be measured using dynamic light scattering, the number of particles in each particle size range can be counted through data analysis, and the D50 value can be calculated from the results. Optionally, the number of particles can be measured using laser diffraction. When measured by laser diffraction, the particles to be measured can be dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasound at an output of approximately 28 kHz at 60 W, and the average size D50 can be calculated based on the 50% particle size distribution using this measuring device.
[0017] Here, when the particles are spherical, the size can refer to the diameter.
[0018] The size can be measured using a particle size analyzer (LS 13 320 XR from Beckman Coulter).
[0019] According to an embodiment, a method for preparing a silicon-carbon composite as a negative electrode active material for rechargeable lithium batteries is provided. This preparation method includes grinding silicon precursor particles to prepare silicon nanoparticles. In this preparation method, only a short grinding time of the silicon precursor particles is required to prepare the silicon nanoparticles. Therefore, this preparation method not only has excellent processability and economic efficiency, but also enables the preparation of silicon-carbon composites with low oxygen concentrations. When the oxygen concentration in the negative electrode active material is high, lithium ions may react with oxygen during battery charge and discharge, reducing battery capacity. As a result, the risk of battery fire or explosion may increase. Oxygen in the negative electrode active material may be incorporated into the negative electrode active material at several stages of the preparation process, but it is most likely to be incorporated during the preparation of silicon nanoparticles by grinding silicon precursor particles.
[0020] The preparation method includes preparing silicon nanoparticles by mixing silicon nanoparticles (or assemblies of silicon nanoparticles) with an amorphous carbon precursor and then subjecting them to heat treatment. The preparation of silicon nanoparticles involves grinding silicon precursor particles in a solvent with a viscosity of 0.1 mPa·s to 0.5 mPa·s at 25 °C.
[0021] The preparation method will be described in detail below.
[0022] Preparation of silicon nanoparticles Silicon nanoparticles were prepared by grinding silicon precursor particles in a solvent.
[0023] Silicon precursor particles can have an average size D50 of a few micrometers. For example, silicon precursor particles can have an average size D50 of 10 μm or smaller (such as 5 μm or smaller or 1 μm or smaller). Silicon precursor particles can be composed of silicon alone.
[0024] In the preparation method, the viscosity of the solvent used in grinding the silicon precursor particles is adjusted at 25°C. Here, the solvent viscosity is a value evaluated using a Brookfield rotational viscometer. The solvent has a viscosity of, for example, 0.1 mPa·s to 0.5 mPa·s at 25°C. When the solvent viscosity at 25°C exceeds 0.5 mPa·s, the excessively high viscosity of the solvent may reduce the number of collisions between the silicon precursor particles and the grinding balls during grinding, thus increasing the grinding time and consequently increasing the oxygen concentration of the negative electrode active material. In a more specific example, the solvent may have a viscosity of 0.1 mPa·s to 0.4 mPa·s at 25°C.
[0025] The solvent can be an oxygen-free solvent. An oxygen-free solvent can also reduce the oxygen content contained in the silicon nanoparticles during the milling of silicon precursor particles.
[0026] In a specific example, the solvent can be n-hexane. n-Hexane increases the fluidity of the grinding balls (especially zirconium balls) during grinding, thereby increasing the number of collisions between the silicon precursor particles and the grinding balls. Therefore, grinding time can be significantly shortened. Additionally, n-hexane promotes the aggregation of silicon precursor particles, increasing the number of collisions with the grinding balls and thus improving the grinding efficiency of the silicon precursor particles. Furthermore, n-hexane allows silicon nanoparticles to aggregate after grinding, enabling the recovery of components from the process. Moreover, n-hexane is beneficial for the preparation of the following negative electrode active materials.
[0027] Milling can be performed after mixing the silicon precursor particles and milling balls in a solvent. In a specific example, based on a total of 100 parts by weight of solvent and silicon precursor particles, the solvent and silicon precursor particles can be included in a weight ratio of 70:30 to 95:5 (solvent:silicon precursor particles). Within this range, silicon nanoparticles can be effectively prepared. In some examples, the weight ratio of solvent to silicon precursor particles can be 80:20 to 95:5, 85:15 to 95:5, or 90:10.
[0028] The grinding can be performed at temperatures ranging from 20°C to 35°C (e.g., 25°C to 35°C). Within these ranges, the preparation efficiency of silicon nanoparticles with the desired average particle size D50 can be high.
[0029] The milling process can last from 10 to 25 hours, for example, 10 to 20 hours or 10 to 16 hours. Within these ranges, the preparation efficiency of silicon nanoparticles with the desired average size D50 can be high.
[0030] Silicon nanoparticles have an average size D50 of 10 nm to 200 nm. Within this range, it can be advantageous to provide negative electrode active materials that achieve excellent battery capacity. For example, silicon nanoparticles can have an average size D50 of 20 nm to 200 nm (e.g., 50 nm to 150 nm or 50 nm to 100 nm).
[0031] In a specific example, silicon nanoparticles can be primary particles, such as single particles that are not aggregates of particles.
[0032] Silicon nanoparticles can be used as is in the preparation of silicon precursors described below, or they can be used in the form of a dispersion comprising silicon nanoparticles (silicon nanoparticle dispersion). The silicon nanoparticle dispersion may include a solvent that is easily volatile and does not oxidize the silicon nanoparticles. For example, as mentioned above, the solvent may be n-hexane. The concentration of silicon nanoparticles in the silicon nanoparticle dispersion may be from 10 wt% to 30 wt%.
[0033] Heat treatment Silicon-carbon composites are prepared by mixing silicon nanoparticles (or assemblies of silicon nanoparticles) with an amorphous carbon precursor and then subjecting them to heat treatment.
[0034] Silicon-carbon composites can be prepared by mixing silicon nanoparticles with an amorphous carbon precursor and then heat-treating them. Alternatively, silicon-carbon composites can be prepared by mixing an assembly of silicon nanoparticles with an amorphous carbon precursor and then heat-treating them. The assembly of silicon nanoparticles can be prepared by spray drying a dispersion of silicon nanoparticles.
[0035] Through spray drying, silicon nanoparticles can be assembled into secondary particles with micron-sized structures. These secondary particles may include pores, such as gaps between silicon nanoparticles.
[0036] Spray drying can adjust the sphericity of the prepared negative electrode active material by adjusting the type of nozzle used for spraying and the atmosphere in which the spray is performed. Using, for example, a two-fluid nozzle can be suitable, which can form fine particles by mixing two fluids, a liquid and a gas. When using a two-fluid nozzle, fine spherical particles can be formed. Because the size of the formed particles is small, no additional pulverization process is required, thus maintaining the spherical shape of the particles. A disc nozzle that sprays while rotating may be unsuitable because it forms large particles and requires an additional pulverization process due to the large particle size, which may result in particles of various shapes (such as spherical, elliptical, annular, etc.).
[0037] Spray drying can be carried out under a nitrogen atmosphere, for example, by flowing nitrogen at a flow rate of 30 L / min to 50 L / min or 30 L / min to 40 L / min (nitrogen blowing). When the nitrogen flow rate is within these ranges, spray drying can form spherical particles of suitable size. Nitrogen flow rates less than 30 L / min may be unsuitable because the sprayed product aggregates, thus increasing the size of the prepared particles. Nitrogen flow rates exceeding 50 L / min may result in particles that are too small and produce a large amount of fine powder.
[0038] Spray drying can be performed at temperatures ranging from 50°C to 170°C. When spray drying is performed within this temperature range, the micron-sized spherical Si particles can be thoroughly dried by instantaneous evaporation because the temperature is sufficiently above the boiling point of the solvent. In some examples, spray drying can be performed at temperatures ranging from 50°C to 150°C.
[0039] Amorphous carbon precursors may be polyimide resins, furan resins, phenolic resins, polyvinyl alcohol resins, poly(meth)acrylic acid resins, polyurethane resins, cellulose resins, epoxy resins, polystyrene resins, petroleum asphalt, coal asphalt, raw coke, mesophase asphalt, coal oil, petroleum heavy oil, coke, or combinations thereof.
[0040] Silicon nanoparticles (or assemblies of silicon nanoparticles) and an amorphous carbon precursor, based on a total of 100 parts by weight, can be included in a weight ratio of 20:80 to 99:1 (silicon nanoparticles (or assemblies of silicon nanoparticles): amorphous carbon). Within this weight ratio range, negative electrode active materials with excellent battery capacity can be prepared. For example, the weight ratio can be 50:50 to 99:1 or 60:40 to 96:4.
[0041] Heat treatment can be performed at 400°C to 1200°C or 700°C to 1000°C. When heat treatment is performed within this temperature range, the negative electrode active material can maintain a spherical shape, the conductivity of the negative electrode active material can be improved by carbonization of amorphous carbon, and the initial efficiency of the battery can be improved.
[0042] The heat treatment can be carried out under a nitrogen atmosphere. As a result of the heat treatment, the amorphous carbon precursor can be converted into amorphous carbon and included as amorphous carbon in the negative electrode active material.
[0043] The mixing and heat treatment with the amorphous carbon precursor can be performed once or more. For example, the mixing and heat treatment with the amorphous carbon precursor can be performed twice or more.
[0044] The method of mixing with the amorphous carbon precursor and heat treatment twice will be described in detail below.
[0045] Initial mixing and heat treatment Silicon nanoparticles (or assemblies of silicon nanoparticles) are mixed with an amorphous carbon precursor and then heat-treated.
[0046] The amorphous carbon precursor can be the same as described above. For example, the amorphous carbon precursor can be mesophase pitch.
[0047] Silicon nanoparticles (or assemblies of silicon nanoparticles) and an amorphous carbon precursor, based on a total of 100 parts by weight, can be included in a weight ratio of 20:80 to 99:1 (silicon nanoparticles (or assemblies of silicon nanoparticles): amorphous carbon precursor). Within this weight ratio range, negative electrode active materials with excellent battery capacity can be prepared. For example, the weight ratio can be 50:50 to 99:1, 60:40 to 96:4, or 90:10 to 99:1.
[0048] Heat treatment can be performed at 400°C to 1200°C, 700°C to 1000°C, or 800°C to 1000°C. When heat treatment is performed within this temperature range, the negative electrode active material can maintain a spherical shape, the conductivity of the negative electrode active material can be improved by carbonization of amorphous carbon, and the initial efficiency of the battery can be improved.
[0049] As mentioned above, heat treatment can be performed under a nitrogen atmosphere.
[0050] Secondary mixing and heat treatment The product prepared by initial mixing and heat treatment is mixed with an amorphous carbon precursor and then heat-treated.
[0051] The amorphous carbon precursor is as described above. For example, the amorphous carbon precursor can be mesophase pitch.
[0052] The product prepared by primary mixing and heat treatment can be mixed and heat treated again with the amorphous carbon precursor either as is or after pulverization.
[0053] The pulverized product and amorphous carbon precursor prepared by initial mixing and heat treatment can be included in a weight ratio of 20:80 to 99.9:0.1 (pulverized product prepared by initial mixing and heat treatment: amorphous carbon precursor) based on a total of 100 parts by weight. Within this weight ratio range, negative electrode active materials providing excellent battery capacity can be prepared. In some examples, this weight ratio can be 50:50 to 99:1, 60:40 to 96:4, or 90:10 to 99.9:0.1.
[0054] Heat treatment can be performed at 400°C to 1200°C, 700°C to 1000°C, or 800°C to 1000°C. When heat treatment is performed within these temperature ranges, the negative electrode active material can maintain a spherical shape, the conductivity of the negative electrode active material can be improved by carbonization of amorphous carbon, and the initial efficiency of the battery can be improved.
[0055] Heat treatment can be carried out under a nitrogen atmosphere.
[0056] Negative electrode active material for rechargeable lithium batteries The following section describes the negative electrode active material for rechargeable lithium batteries.
[0057] The negative electrode active material used in rechargeable lithium batteries includes silicon-carbon composites, which consist of silicon nanoparticles and amorphous carbon, and have an oxygen content of 10% or less.
[0058] The negative electrode active material has an oxygen content of 10% or less. Therefore, the degree to which lithium ions react with oxygen is low during the charging and discharging of a battery including this negative electrode active material. Consequently, battery capacity can be increased, and the risk of battery explosion in the event of a fire can be reduced. In some examples, the negative electrode active material may have an oxygen content of 0 to 10%, or greater than 0 and 10% or less (e.g., 0, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%).
[0059] The negative electrode active material can be prepared using the methods described above.
[0060] In a specific example, the negative electrode active material may include a core comprising silicon nanoparticles and amorphous carbon. An amorphous carbon coating layer may surround the core.
[0061] In a specific example, the negative electrode active material can be a two-component negative electrode active material containing silicon and amorphous carbon.
[0062] The interparticle distance between silicon nanoparticles included in the core of the negative electrode active material can be 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 65 nm or less, 60 nm or less, 55 nm or less, 50 nm or less, 45 nm or less, 40 nm or less, or 35 nm or less. When the interparticle distance between silicon nanoparticles falls within these ranges, the size of the pores included in the core and the total pore volume can be reduced. Furthermore, when the interparticle distance between silicon nanoparticles falls within the aforementioned ranges, the volume of pores present within the negative electrode active material can be reduced, and electrolyte permeation into the core during battery operation can be prevented by reducing the interparticle distance between silicon nanoparticles. As a result, side reactions between the electrolyte and the negative electrode active material can be suppressed, thereby improving the lifespan of the battery including the negative electrode active material.
[0063] Here, the interparticle distance between silicon nanoparticles refers to the distance between the centers of silicon nanoparticles. The interparticle distance between silicon nanoparticles can refer to the interparticle distance between 50% to 100% (e.g., 60% to 100%, 70% to 100%, or 80% to 100%) of the total number of silicon nanoparticles included in the core within the above range.
[0064] Silicon nanoparticles can have an average size D50 of 10 nm to 200 nm (e.g., 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, 170 nm, 175 nm, 180 nm, 185 nm, 190 nm, 195 nm, 200 nm, 20 nm to 200 nm, or greater than or equal to 50 nm, 60 nm, 70 nm or 80 nm and less than or equal to 100 nm or 90 nm). When the average size D50 of silicon nanoparticles is within these ranges, side reactions with the electrolyte are suppressed and the expansion of the silicon nanoparticles is reduced. Therefore, initial efficiency and lifetime characteristics can be improved.
[0065] Silicon nanoparticles can possess a full width at half maximum (FWHM) of the (111) plane at X-ray diffraction angles (2θ) ranging from 0.3° to 7° using CuKα rays. This can improve lifetime characteristics. The FWHM of the (111) plane of silicon nanoparticles at X-ray diffraction angles (2θ) using CuKα rays can be adjusted by changing the silicon particle size or the silicon nanoparticle fabrication process.
[0066] The aspect ratio (i.e., the ratio of the major axis length (b) to the minor axis length (a)) of silicon nanoparticles can be from 2 to 8, for example, from 2 to 6. Furthermore, silicon nanoparticles can have a minor axis length (a) of 20 nm to 50 nm and a major axis length (b) of 50 nm to 300 nm. When the aspect ratio, major axis length (b), and minor axis length (a) of silicon nanoparticles fall within these ranges, side reactions between the negative electrode active material and the electrolyte are suppressed, and the expansion of the silicon nanoparticles is reduced. Therefore, initial efficiency and lifetime characteristics can be improved.
[0067] Based on the total weight of the negative electrode active material, silicon nanoparticles can be included in amounts of 20wt% to 80wt%, 30wt% to 70wt%, 30wt% to 60wt%, or 30wt% to 50wt%. When the amount of silicon nanoparticles falls within the above ranges, the battery capacity can be improved.
[0068] The amorphous carbon included in the core can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, or a combination thereof.
[0069] When amorphous carbon is included in the core, the pore volume of the negative electrode active material decreases, thus suppressing side reactions with the electrolyte. Furthermore, when silicon nanoparticles in the negative electrode active material expand, the amorphous carbon can buffer this expansion to suppress the expansion of the surrounding battery. Additionally, amorphous carbon can act as a binder to mitigate the breakage of the negative electrode active material, thereby effectively maintaining its shape.
[0070] The coating layer comprises amorphous carbon and can have a thickness of 1 nm to 900 nm (e.g., 5 nm to 800 nm). This thickness reduces the specific surface area of the negative electrode active material and prevents electrolyte from flowing into it. Consequently, side reactions with the electrolyte can be minimized, and battery life characteristics can be improved. The amorphous carbon included in the coating layer can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, or a combination thereof, and can be the same as or different from the amorphous carbon included in the core.
[0071] Based on the total weight of the negative electrode active material, amorphous carbon can be included in an amount of 20 wt% to 80 wt% (e.g., 20 wt% to 70 wt%, 20 wt% to 60 wt%, 20 wt% to 50 wt%, or 20 wt% to 40 wt%). When the amount of amorphous carbon falls within these ranges, side reactions between the negative electrode active material and the electrolyte can be suppressed.
[0072] According to one embodiment, the negative electrode active material can have an average particle size D50 of 2 μm to 15 μm (e.g., 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 3 μm to 13 μm, or 5 μm to 10 μm). When the average particle size of the negative electrode active material falls within these ranges, lithium ions can easily diffuse into the negative electrode active material, and the resistance and rate characteristics of the battery including the negative electrode active material can be improved. Furthermore, excessive increase in the specific surface area of the negative electrode active material can be suppressed to reduce side reactions with the electrolyte. The average size D50 of the negative electrode active material can be adjusted by regulating the disintegration and pulverization conditions during the preparation of the negative electrode active material.
[0073] In the negative electrode active material, the total volume of pores with a size of 200 nm or smaller can be 3.0 × 10⁻⁶. -2 cm 3 / g or less, for example, 2.5 × 10 -2 cm 3 / g or less, 2.3×10 -2 cm 3 / g or less, 2.0×10 -2 cm 3 / g or less, 1.9×10 -2 cm 3 / g or less, 1.8×10 -2 cm 3 / g or less, 1.7×10 -2 cm 3 / g or less, 1.6×10 -2 cm 3 / g or less, 1.5×10 -2 cm 3 / g or less, 1.4×10 -2 cm 3 / g or less, 1.3×10 -2 cm 3 / g or less, 1.2×10 -2 cm 3 / g or less, 1.1×10 -2 cm 3 / g or less, 1.0×10 -2 cm 3 / g or less, 0.9×10 -2 cm 3 / g or less, 0.8×10 -2 cm 3 / g or less, 0.7×10 -2 cm 3 / g or less, 0.6×10 -2 cm 3 / g or less, or 0.5×10 -2 cm 3 / g or less. Within these ranges, side reactions between the electrolyte and silicon nanoparticles can be suppressed to improve initial efficiency and lifetime characteristics. The total volume of pores with a size of 200 nm or smaller can be quantitatively measured using a Barrett-Joyner-Halenda (BJH) analyzer.
[0074] The negative electrode active material can have a pore size of 200 nm or smaller (e.g., 170 nm or smaller, 150 nm or smaller, 130 nm or smaller, 100 nm or smaller, or 50 nm or smaller). When the pore size is controlled within these ranges, side reactions between the electrolyte and silicon nanoparticles can be reduced, and batteries with improved initial efficiency and lifetime characteristics can be obtained.
[0075] The negative electrode active material can have 10m 2A Brunauer-Emmett-Teller (BET) specific surface area of / g or less. When the BET specific surface area falls within this range, side reactions with the electrolyte are suppressed, thus improving the efficiency of the battery, including the negative electrode active material.
[0076] Based on a total of 100 parts by weight of silicon nanoparticles and amorphous carbon in the negative electrode active material, the silicon nanoparticles and amorphous carbon can be included in a weight ratio of 80:20 to 20:80 (e.g., 70:30 to 30:70, 70:30 to 40:60, or 70:30 to 50:50). When the amount of silicon nanoparticles and amorphous carbon is within these ranges, the internal pore volume can be reduced, and the amorphous carbon can be uniformly dispersed inside and on the surface of the negative electrode active material. As a result, side reactions with the electrolyte can be suppressed, and the performance of the negative electrode active material can be improved.
[0077] In specific examples, the negative electrode active material may have a sphericity of 0.7 or greater (e.g., 0.7 or greater and 1.0 or less). Here, sphericity refers to the ratio (Lb / La) of the minor axis length (Lb) to the major axis length (La) when the negative electrode active material has a spherical or elliptical shape. A sphericity of 1.0 means that the negative electrode active material has a substantially perfect spherical shape; therefore, it is widely understood by those skilled in the art that the maximum sphericity is 1.0 and that the sphericity may not exceed 1.0. When the sphericity of the negative electrode active material is 0.7 or greater, the surface area of the negative electrode active material can be reduced, thus reducing the area of the negative electrode active material in contact with the electrolyte or the area of the negative electrode active material reacting with lithium. As a result, side reactions with the electrolyte and reactions with lithium can be reduced, and the active material can expand uniformly in the negative electrode, thereby reducing the resulting volume expansion. In other examples, the negative electrode active material may have an elliptical or spherical profile.
[0078] When the BET specific surface area of the negative electrode active material is 10m² 2 / g or less (e.g., 0.5m) 2 / g to 10m 2 When the BET specific surface area of the negative electrode active material is 10 m² / g, the effect of the reduced surface area is more pronounced. 2 When the concentration is / g or less, contact with the electrolyte is reduced, thereby suppressing side reactions. Therefore, this range can help improve performance and increase initial efficiency.
[0079] In summary, the negative electrode active material according to the embodiments has a sphericity of 0.7 or greater and a BET specific surface area of 10 m². 2 / g or less, thus it can be an active material with reduced side reactions with electrolytes and reduced reactions with lithium.
[0080] In the negative electrode active material, silicon nanoparticles are primary particles and can be included in the silicon-carbon composite as secondary particles, which are aggregates of primary particles, i.e., one or more primary particles. Therefore, the silicon-carbon composite can include secondary particles formed by assembling Si nanoparticles.
[0081] In some embodiments, silicon nanoparticles may have a sheet-like shape, a spherical shape, etc. However, the shape of silicon nanoparticles is not limited to these. Furthermore, secondary particles formed by assembling one or more primary particles may have a spherical shape.
[0082] Amorphous carbon can cover the surface of the secondary particles. In other words, the negative electrode active material may include a core containing silicon nanoparticles (e.g., a secondary particle core formed by assembling primary particles as silicon nanoparticles) and amorphous carbon surrounding the core. In embodiments, the core refers to a region located within the negative electrode active material, and more specifically, a region surrounded by amorphous carbon and substantially not exposed to the outside. Therefore, the core can be viewed as a region located within the amorphous carbon.
[0083] Amorphous carbon can also fill the gaps between primary particles. When amorphous carbon fills these gaps, it covers the surface of the primary particles. Thus, the pore volume of the negative electrode active material decreases, thereby suppressing side reactions with the electrolyte. Furthermore, when the primary particles, which are silicon nanoparticles, expand, the amorphous carbon acts as a buffer against this expansion. Additionally, the amorphous carbon filling the gaps between primary particles acts as a binder, preventing the particles of the negative electrode active material from breaking apart. As a result, conductivity is improved.
[0084] Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbides, calcined coke, or a combination thereof.
[0085] Silicon nanoparticles can have a flake-like shape. In other words, silicon nanoparticles can have a long axis to short axis ratio (e.g., width to thickness ratio) of 5 to 20. When the long axis to short axis ratio of the silicon particles falls within such a range, the expansion of the Si nanoparticles can be reduced. Therefore, the initial efficiency and lifetime characteristics of batteries including this negative electrode active material can be improved.
[0086] The particle size of silicon nanoparticles can range from 10 nm to 200 nm, for example, from 20 nm to 200 nm or from 20 nm to 100 nm. The particle size can be an average particle size. Here, the average particle size can refer to the particle size D50 measured based on cumulative volume. As mentioned above, unless otherwise defined herein, the average particle size D50 refers to the particle size corresponding to 50% of the cumulative volume in the particle size distribution. When the size of the Si nanoparticles falls within the above range, side reactions between the negative electrode active material and the electrolyte are suppressed, and the expansion of the Si nanoparticles is reduced. Therefore, the initial efficiency and lifetime characteristics of batteries including negative electrode active materials can be improved.
[0087] When silicon nanoparticles are secondary particles formed by assembling one or more primary particles, the particle size of the secondary particles can be from 2 μm to 15 μm, for example, from 5 μm to 10 μm. The particle size of the primary particles can be from 10 nm to 200 nm. When the average particle size of the silicon nanoparticles included in the negative electrode active material falls within these ranges, lithium ions can easily diffuse into the negative electrode active material. Furthermore, resistance and rate performance can be improved.
[0088] In this embodiment, the full width at half maximum (FWHM(111)) of the diffraction peak of the (111) plane of the silicon particle can be the full width at half maximum when the X-ray diffraction angle (2θ) is between 0.3 degrees (°) and 7° when measured by X-ray diffraction using CuKα rays. When the FWHM(111) of the Si particle is within this range, the lifetime characteristics of the battery, including the negative electrode active material containing the silicon particle, can be improved. Here, the X-ray diffraction measurement uses CuKα rays as the target ray and is performed under measurement conditions of a 2θ range of 40° to 50°, a scan rate of 0.04° / s to 0.06° / s, and a step size of 0.01° / step to 0.03° / step.
[0089] The weight ratio of silicon nanoparticles to amorphous carbon can be 8:2 to 2:8 or 7:3 to 5:5. In some embodiments where silicon nanoparticles exist in the negative electrode active material in the form of secondary particles formed by assembling silicon nanoparticles, the mixing ratio of silicon nanoparticles and amorphous carbon can also be considered as the mixing ratio of secondary particles to amorphous carbon. When the mixing ratio of silicon nanoparticles and amorphous carbon falls within the above ranges, better capacity, especially higher capacity, can be provided compared to crystalline carbon negative electrode active materials.
[0090] Amorphous carbon can exist as a coating layer on the surface of secondary particles. In addition to the coating layer form, amorphous carbon can also fill the gaps between primary particles. However, regardless of whether amorphous carbon fills the gaps between primary particles, exists as a coating layer, or exists in any other form, the total amount of amorphous carbon included in the negative electrode active material can be from 20 wt% to 80 wt% based on a total of 100 wt% of the negative electrode active material.
[0091] When amorphous carbon is present as a coating layer covering and surrounding the surface of secondary particles, the amorphous carbon coating layer on the surface of the secondary particles can have a thickness of 1 nm to 1000 nm (e.g., 30 nm to 200 nm). When the thickness of the amorphous carbon coating layer is within these ranges, the conductivity of the negative electrode active material can be improved. Furthermore, due to the reduced contact with the electrolyte, the increase in resistance caused by the generation of by-reaction products can be effectively suppressed.
[0092] The negative electrode active material can have a particle size of 40 μm or smaller (e.g., 2 μm to 15 μm). When the particle size of the negative electrode active material falls within this range, lithium ions can easily diffuse into the negative electrode active material, which can improve battery resistance and rate characteristics.
[0093] Rechargeable lithium batteries The following describes a rechargeable lithium battery. A rechargeable lithium battery includes a negative electrode and a positive electrode, the negative electrode comprising the negative electrode active material described herein for the rechargeable lithium battery.
[0094] The negative electrode may include a current collector and a negative electrode active material layer on the current collector. The negative electrode active material layer includes the negative electrode active material for rechargeable lithium batteries as described above.
[0095] In a specific example, the negative electrode active material may be at least 95 wt% (e.g., 95 wt% to 100 wt%) of the total negative electrode active material within the negative electrode active material layer. In addition to the aforementioned negative electrode active material (first negative electrode active material), the negative electrode active material layer may also include different negative electrode active materials (second negative electrode active materials).
[0096] The negative electrode for a rechargeable lithium-ion battery may include a current collector and a layer of negative electrode active material on the current collector. The negative electrode active material layer may include negative electrode active material and may also include a binder and / or a conductive material (e.g., an electrically conductive material). For example, the negative electrode active material layer may include about 90 wt% to about 99 wt% of negative electrode active material, about 0.5 wt% to about 5 wt% of binder, and about 0 wt% to about 5 wt% of conductive material.
[0097] The negative electrode active material includes the negative electrode active material as described above. In a specific example, the negative electrode active material may be included in an amount of 95 wt% or more (e.g., 95 wt% to 100 wt%, or 100 wt%) of the total negative electrode active material in the negative electrode active material layer.
[0098] The second negative electrode active material may include a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0099] The material capable of reversibly intercalating / deintercalating lithium ions may include a carbon-based negative electrode active material, for example, crystalline carbon, amorphous carbon, or a combination thereof. The crystalline carbon may be graphite, such as amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, and the like.
[0100] The lithium metal alloy includes an alloy of lithium and a metal (or metalloid) selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn.
[0101] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy. In the formula Si-Q, Q is selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof. The Sn-based negative electrode active material may include Sn, SnO₂, a Sn-based alloy, or a combination thereof.
[0102] The silicon-carbon composite may be a composite of silicon and amorphous carbon. In some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) assembled from primary silicon particles and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the primary silicon particles. The secondary particles may be dispersed in an amorphous carbon matrix.
[0103] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core.
[0104] The Si-based negative electrode active material or the Sn-based negative electrode active material may be used in combination with the carbon-based negative electrode active material.
[0105] The binder can be used to adhere negative electrode active material particles to each other, and also to adhere negative electrode active material to the current collector. The binder can include non-aqueous binders, aqueous binders, dry binders, or combinations thereof.
[0106] Non-aqueous adhesives may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0107] Waterborne adhesives may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0108] When an aqueous binder is used as the negative electrode binder, it may also include a cellulose compound capable of imparting viscosity. The cellulose compound may include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or an alkali metal salt thereof. The alkali metal may include Na, K, or Li.
[0109] Dry adhesives can be polymeric materials capable of taking the form of fibers. For example, dry adhesives can be polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0110] Conductive materials can be used to impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause undesirable chemical changes in a rechargeable lithium-ion battery and conducts electrons can be used as a conductive material. Non-limiting examples of conductive materials include: carbon-based materials such as natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials in the form of metal powders or metal fibers, including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0111] The negative electrode current collector may include copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0112] positive electrode The positive electrode for a rechargeable lithium-ion battery may include a current collector and a layer of positive electrode active material on the current collector. The positive electrode active material layer may include positive electrode active material and may also include a binder and / or a conductive material. The positive electrode may also include additives that can be used as a sacrificial positive electrode.
[0113] The positive electrode active material may include compounds capable of intercalating and deintercalating lithium (lithium-intercalating compounds). Specifically, at least one of the composite oxides of lithium with metals selected from cobalt, manganese, nickel, and combinations thereof may be used.
[0114] The composite oxide can be a lithium transition metal composite oxide. Examples of composite oxides include lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, cobalt-free lithium nickel manganese oxides, or combinations thereof.
[0115] As a specific example, the following compounds, represented by any of the following chemical formulas, can be used: Li a A 1- b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, and 0<α<2); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0≤e≤0.1); Li a NiG bO2 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a Mn 1-b G b O2 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8, and 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90 ≤ a ≤ 1.8, and 0 ≤ g ≤ 0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); or Li a FePO4 (0.90≤a≤1.8). In the above chemical formula, A is Ni, Co, Mn or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements or a combination thereof; D is O, F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; and L 1 It is Mn, Al, or a combination thereof.
[0116] The positive electrode active material can be, for example, a high-nickel positive electrode active material. Based on 100 mol% of metals other than lithium in the lithium transition metal complex oxide, the high-nickel positive electrode active material can have a nickel content of greater than or equal to about 80 mol%, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. High-nickel positive electrode active materials can provide high capacity and can be used in high-capacity, high-density rechargeable lithium batteries.
[0117] Based on a 100wt% positive electrode active material layer, the amount of positive electrode active material can be from about 90wt% to about 99.5wt%. Based on the 100wt% positive electrode active material layer, the amounts of binder and conductive material can be from about 0.5wt% to about 5wt%, respectively.
[0118] The binder is used to adhere the positive electrode active material particles to each other, and also to adhere the positive electrode active material to the current collector. As a non-limiting example, examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, nylon, etc.
[0119] Conductive materials can be used to impart conductivity (e.g., electrical conductivity) to electrodes. Any material that does not cause undesirable chemical changes and conducts electrons in a rechargeable lithium-ion battery can be used as a conductive material in the battery. Examples of conductive materials can include: carbon-based materials such as natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials in the form of metal powders or metal fibers, including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0120] Aluminum can be used as a current collector, but this disclosure is not limited thereto.
[0121] The rechargeable lithium battery may further include an electrolyte. The electrolyte may include a non-aqueous organic solvent and a lithium salt.
[0122] Non-aqueous organic solvents can be used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or combinations thereof.
[0123] Carbonate solvents can include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.
[0124] Ester solvents can include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, caprolactone, etc. Ether solvents can include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Additionally, ketone solvents can include cyclohexanone, etc. Alcohol solvents can include ethanol, isopropanol, etc. Aprotic solvents can include nitriles, such as R-CN (where R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether bonds, etc.); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.
[0125] Non-aqueous organic solvents can be used alone or in combination of two or more. Furthermore, when using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0126] Lithium salts dissolved in organic solvents supply lithium ions in batteries, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(CyF 2y+1 At least one of the following: (SO2) (where x and y are integers from 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).
[0127] Depending on the type of rechargeable lithium battery, a separator may be present between the positive and negative electrodes. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or multilayer films of two or more layers thereof (e.g., hybrid multilayer films such as polyethylene / polypropylene bilayer separators, polyethylene / polypropylene / polyethylene trilayer separators, polypropylene / polypropylene / polypropylene trilayer separators, etc.)).
[0128] The membrane may include a porous substrate and a coating layer on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.
[0129] Porous substrates can be made from a selection of polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyetherketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene ethers, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (TEFLON). ® A polymer film formed from at least one of the polymers or copolymers or mixtures of two or more of them.
[0130] Organic materials may include polymers such as polyvinylidene fluoride or (meth)acrylic acid polymers. Inorganic materials may include inorganic particles selected from Al₂O₃, SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, GaO, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, and combinations thereof. However, this disclosure is not limited to these examples.
[0131] Organic and inorganic materials can be mixed in a coating layer, or a coating layer containing organic materials and a coating layer containing inorganic materials can be stacked.
[0132] Rechargeable lithium batteries can be cylindrical, prismatic, pouch-shaped, or coin-shaped, depending on their shape.
[0133] Figures 1 to 4 This is a schematic diagram of a rechargeable lithium battery according to an embodiment. Figure 1 A cylindrical battery is shown. Figure 2 A prismatic battery is shown. Figure 3 and Figure 4 A pouch-type battery is shown. (See reference) Figures 1 to 4 The rechargeable lithium battery 100 may include an electrode assembly 40 comprising a separator 30 between a positive electrode 10 and a negative electrode 20, and a housing 50 therein housing the electrode assembly 40. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated with an electrolyte. Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of the sealed housing 50. (As illustrated...) Figure 2 As shown, the rechargeable lithium battery 100 may include a positive lead terminal 11, a positive terminal 12, a negative lead terminal 21, and a negative terminal 22. Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 may include electrode terminals 70 forming electrical paths for guiding current formed in the electrode assembly 40 to the outside of the battery. The electrode terminals 70 may be, for example, a positive electrode terminal 71 and a negative electrode terminal 72.
[0134] As a non-limiting example, the rechargeable lithium battery according to the embodiments can be used in automobiles, mobile phones and / or various types of electronic devices.
[0135] Examples and comparative examples of this disclosure will be described below. However, the following examples are merely illustrative of this disclosure, and this disclosure is not limited to the following examples.
[0136] Example 1 Hexane and silicon precursor particles (average size D50: approximately 1 μm) were mixed at a weight ratio of 90:10, and the resulting mixture was milled in a bead mill with zirconium balls for 12 hours to prepare a silicon nanoparticle dispersion. The viscosity of hexane at 25 °C, measured using a Brookfield rotational viscometer, was 0.5 mPa·s. The prepared dispersion was spray-dried at 100 °C to prepare silicon secondary particles assembled from silicon nanoparticles. The prepared silicon secondary particles and mesophase pitch were mixed at a weight ratio of 95.5:4.5 and heat-treated at 900 °C for 1 hour under a N2 atmosphere to obtain the product. The obtained product was pulverized to obtain a pulverized product, and the pulverized product was mixed with mesophase pitch (i.e., amorphous carbon) at a weight ratio of 99.5:0.5 and heat-treated at 900 °C for 1 hour under a nitrogen atmosphere to prepare the negative electrode active material.
[0137] The negative electrode active material is a silicon-carbon composite comprising a core containing silicon nanoparticles and amorphous carbon. An amorphous carbon coating layer surrounds the core. Based on a total of 100 parts by weight of silicon nanoparticles and amorphous carbon, the negative electrode active material comprises silicon nanoparticles and amorphous carbon in a weight ratio of 90:10, and the average size D50 of the negative electrode active material is 10 μm.
[0138] A negative electrode active material slurry was prepared by mixing 97.5 wt% of the prepared negative electrode active material and 2.5 wt% of (meth)acrylic acid binder (a copolymer of acrylic acid and acrylonitrile) and styrene-butadiene rubber (SBR) (1.5 wt% and 1 wt%, respectively) in distilled water. The negative electrode active material slurry was coated onto copper foil, dried, and then rolled to fabricate the negative electrode. A half-cell battery was fabricated using the negative electrode, lithium metal counter electrode, and electrolyte. The electrolyte was a mixed solvent (volume ratio: 3:7) of ethylene carbonate and dimethyl carbonate dissolved in 1 M LiPF6.
[0139] Example 2 Except for the 16-hour grinding process, the negative electrode active material and battery are manufactured in the same manner as in Example 1.
[0140] Comparison Example 1 The negative electrode active material and battery were manufactured in the same manner as in Example 1, except that isopropanol (viscosity at 25°C: 1.9 mPa·s) was used as the grinding solvent.
[0141] (Experiment 1) Evaluation of the active material of the negative electrode Oxygen concentration of negative electrode active material (unit: %): The oxygen concentration of the negative electrode active material was evaluated by measuring the amount of oxygen content generated during the heat treatment of the negative electrode active material using a CS-d analyzer from Eltra GmbH.
[0142] (Experiment 2) Evaluation of battery characteristics The manufactured half-cell battery was charged and discharged at 0.1C, and the charge / discharge capacity was measured. The measured discharge capacity was divided by the amount of active material in the negative electrode to calculate the specific capacity, and the charge / discharge efficiency (the ratio of discharge capacity to charge capacity) was measured.
[0143] The following operations were performed on the half-cell battery, and the charging characteristics were calculated: one cycle of charging at 0.2C constant current (CC) and constant voltage (CV) and discharging at 0.2C; one cycle of charging at 0.5C constant current (CC) and discharging at 0.2C; one cycle of charging at 1C constant current (CC) and discharging at 0.2C; and one cycle of charging at 2C constant current (CC) and discharging at 0.2C. In this case, charging was performed under constant current (CC) conditions with a 10mV cutoff and constant voltage (CV) conditions with a 15-hour cutoff, and discharging was performed under a 1.5V cutoff condition. The charging characteristics at each C rate were measured. The charging characteristic results are expressed as the ratio of the 2C CC charging capacity to the 0.2C CC charging capacity.
[0144] Table 1
[0145] *Silicon nanoparticles: Silicon nanoparticles prepared by grinding.
[0146] As shown in Table 1, the example negative electrode active material exhibits a low oxygen concentration and can be prepared with a shortened grinding time.
[0147] According to embodiments of this disclosure, a method for preparing a negative electrode active material for a rechargeable lithium-ion battery is provided, which improves processability by shortening the grinding time of silicon precursor particles used to prepare silicon nanoparticles. According to other embodiments of this disclosure, a negative electrode active material for a rechargeable lithium-ion battery is provided, which improves battery capacity due to a low oxygen concentration caused by a shortened grinding time of silicon in the preparation of silicon nanoparticles.
[0148] Exemplary embodiments of this disclosure have been described, but this disclosure is not limited thereto.
Claims
1. A negative electrode active material for a rechargeable lithium battery, the negative electrode active material comprising: Silicon-carbon composites, including silicon nanoparticles and amorphous carbon, The silicon-carbon composite has an oxygen content of 10% or less, and The silicon nanoparticles have an average size D50 of 10 nm to 200 nm.
2. The negative electrode active material according to claim 1, wherein, The negative electrode active material comprises: (i) a core comprising the silicon nanoparticles and the amorphous carbon; and (ii) an amorphous carbon coating layer surrounding the core and comprising the amorphous carbon.
3. The negative electrode active material according to claim 1, wherein, The amorphous carbon is soft carbon, hard carbon, mesophase pitch carbide, calcined coke, or a combination thereof.
4. The negative electrode active material according to claim 1, wherein, Based on a total of 100 parts by weight of the silicon nanoparticles and the amorphous carbon in the negative electrode active material, the weight ratio of the silicon nanoparticles to the amorphous carbon is 80:20 to 20:
80.
5. The negative electrode active material according to claim 1, wherein, The negative electrode active material has an average size D50 of 2 μm to 15 μm.
6. A method for preparing a negative electrode active material for a rechargeable lithium battery, the method comprising the following steps: Preparation of silicon nanoparticles; as well as The silicon nanoparticles or the assembly of the silicon nanoparticles are mixed with an amorphous carbon precursor and then subjected to heat treatment. The step of preparing the silicon nanoparticles includes grinding silicon precursor particles in a solvent with a viscosity of 0.1 mPa·s to 0.5 mPa·s at 25°C.
7. The method according to claim 6, wherein, The solvent is n-hexane.
8. The method according to claim 6, wherein, Based on a total of 100 parts by weight of the solvent and the silicon precursor particles, the weight ratio of the solvent to the silicon precursor particles is from 70:30 to 95:
5.
9. The method according to claim 6, wherein, The grinding is carried out at 20°C to 35°C for 10 to 25 hours.
10. The method according to claim 6, wherein, The silicon nanoparticles have an average size D50 of 10 nm to 200 nm.
11. The method according to claim 6, wherein, The steps of mixing the silicon nanoparticles or the assembly of the silicon nanoparticles with the amorphous carbon precursor and the heat treatment step are performed two or more times.
12. The method according to claim 11, further comprising the following step: The silicon nanoparticles or the assembly of the silicon nanoparticles are initially mixed with the amorphous carbon precursor and then subjected to heat treatment. as well as The pulverized product prepared by the initial mixing and heat treatment steps is mixed a second time with the amorphous carbon precursor and then subjected to heat treatment.
13. The method according to claim 12, wherein, In the initial mixing and heat treatment steps: (i) Based on a total of 100 parts by weight of the silicon nanoparticles and the amorphous carbon precursor, the weight ratio of the silicon nanoparticles or the assembly of the silicon nanoparticles to the amorphous carbon precursor is 20:80 to 99:1, and (ii) The heat treatment is carried out in a nitrogen atmosphere at 400°C to 1200°C.
14. The method according to claim 12, wherein, In the secondary mixing and heat treatment steps: (i) Based on a total of 100 parts by weight of the pulverized product and the amorphous carbon precursor, the weight ratio of the pulverized product to the amorphous carbon precursor prepared by the initial mixing and heat treatment steps is 20:80 to 99.9:0.1, and (ii) The heat treatment is carried out in a nitrogen atmosphere at 400°C to 1200°C.
15. A rechargeable lithium battery, said rechargeable lithium battery comprising: The negative electrode includes the negative electrode active material for a rechargeable lithium battery according to any one of claims 1 to 5. as well as Positive electrode.
16. A rechargeable lithium battery, said rechargeable lithium battery comprising: The negative electrode comprises a negative electrode active material for a rechargeable lithium battery prepared by the method according to any one of claims 6 to 14. as well as Positive electrode.
Citation Information
Patent Citations
Apparatus for monitoring remotely container using digital-twin
KR1020250057549A
